Comparison of the reticulospinal drive to lumbar erector spinae muscles in postural and voluntary tasks using the StartReact paradigm - Pouliot, Jeremy; Provencher, Janie; Cherif, Amira; Desmons, Mikaël; Sharp, Andréanne; Fournier, Philippe; Cancino, Edith Elgueta; Chiou, Shin-Yi; Massé-Alarie, Hugo (Frontiers in Human Neuroscience, 2025)
IntroductionWhile lesion and neurophysiological animal studies point toward a notable involvement of subcortical pathways in the control of low back muscles, little attention has been dedicated to the subject in humans. The StartReact paradigm may allow to indirectly test the potential contribution of the reticulospinal system during motor control, thus addressing this gap of knowledge. In this study, we aimed to compare the potential contribution of the reticulospinal system in the control of low back muscles during voluntary (lumbar spine extension) and postural (upper limb movement eliciting anticipatory postural adjustment) tasks using the StartReact paradigm.MethodsThe reaction time (RT) of the lumbar erector spinae was measured within a simple precued RT task while conditioned by startling (SAS—116 dB) or non-startling (NSAS—80 dB) acoustic stimuli.ResultsThe reduction in RT was similar during the postural and voluntary tasks. However, RT was more shortened with the SAS condition compared to the NSAS condition in both tasks. This finding was replicated using a cumulative distribution functions analysis.DiscussionFor the first time, a StartReact effect of back muscles was demonstrated during a voluntary task and was shown to be similar to that observed in a postural task. Therefore, these results suggest a contribution of the reticulospinal tract in the postural and voluntary control of back muscles in humans.